(untitled) - Flint, Mary Louise (Berkeley, Calif., 2002)
This book is the best-ever practical guide to the identification and biology of beneficial organisms that control pests. Growers, pest control advisers, landscape professionals, home gardeners, pest management teachers and students, and anyone fascinated by natural enemies and their prey will want this book to find, identify, and use natural enemies to control pests in almost any agricultural crop, garden, or landscape. The Natural Enemies Handbook is superbly illustrated with 180 high-quality color photographs and 140 expertly rendered drawings, showing hundreds of predators, parasites, and pathogens that attack pest insects, mites, nematodes, plant pathogens, and weeds. The handy Quick Guide allows readers to locate natural enemies that they are likely to find on almost any crop or in the garden and landscape. They can then go to the main text for clear, detailed information.
Keywords: Pests,Sâu bọ,Sâu bọ,Pests; Integrated control,Kiểm soát sinh học,Kiểm soát tổng hợp,Biological control